Research on application of bromelain and alcalase for production of hydrolyzed powder from round scads (Decaterus punctatus) - Le, Tat Thanh; Do , Thi Thanh Trung; Do, Ngoc Minh Giang; Pham, Thu Hue; Huynh, Thi Thu Hue (Vietnam Journal of Marine Science and Technology, 2024)
Round scad (Decaterus punctatus) is a species with high nutritional value and is used mainly as food for humans, and partly as food for aquatic animals. There are no processed products from scad fish in our country; thus, the value of scad fish products still needs to be higher. In this report, we have established the hydrolysis procedure by the enzyme mixture of bromelain and alcalase with the following conditions: the enzyme alcalase/bromelain ratio of 1/3; the enzyme and substrate ratio of 1%; hydrolysis temperature at 50oC; nature pH of fish; the incubated time of 6 h; the speed of 200 rpm; The hydrolyzed powder product is rich in protein (74.5%), and minerals (calcium, potassium, phosphorus, copper), thus has many potential applications in functional foods.